Phylogeographic analyses of Acacia karina (Fabaceae) support long term persistence of populations both on and off banded iron formations - Funnekotter, A.; Millar, M.; Krauss, S.; Nevill, Paul (C S I R O Publishing, 2018)
Understanding the response of species to past climatic changes and whether particular areas acted as refugia is critical both to our understanding of the distribution of genetic variation, and for the conservation and/or restoration of species. We used phylogeographical analyses of Acacia karina, a Banded Iron Formation (BIF) associated species, to better understand historical processes in the semiarid midwest region of Western Australia. We specifically examined whether BIF acted as refugia for the species during the colder, dryer periods of the Quaternary. The genetic structure over the entire range of A. karina was assessed using seven nuclear microsatellites (19 populations; n = 371) and 3196 bp of chloroplast sequence (19 populations; n = 190). We found high levels of nuclear and chloroplast genetic diversity and high levels of chloroplast haplotype differentiation. Genetic diversity was higher than expected for such a geographically restricted species, and similarly high levels of nuclear and chloroplast diversity were observed in BIF and non-BIF populations. The chloroplast and nuclear data suggest that BIFs have not acted as climate refugia for A. karina. Instead, long-term persistence of both BIF and non-BIF populations is supported.